2011
DOI: 10.1111/j.1750-3841.2011.02130.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish Protein Decreases Serum Cholesterol in Rats by Inhibition of Cholesterol and Bile Acid Absorption

Abstract: Fish protein has been shown to decrease serum cholesterol content by inhibiting absorption of cholesterol and bile acid in laboratory animals, though the mechanism underlying this effect is not yet fully understood. The purpose of this study was to elucidate the mechanism underlying the inhibition of cholesterol and bile acid absorption following fish protein intake. Male Wistar rats were divided into 2 dietary groups of 7 rats each, 1 group receiving a diet consisting of 20% casein and the other receiving a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 45 publications
4
72
0
Order By: Relevance
“…Studies suggests that there are other components in fish such as fish proteins that may be beneficial to human health and affect risk factors leading to CVD, beyond n-3 fatty acids (15)(16)(17)(18) . This is supported by results from animal studies showing that fish proteins may have a lowering effect on TAG and cholesterol as well as improve glucose tolerance (19)(20)(21)(22)(23)(24)(25)(26) . In line with this, we have recently shown that supplementation with cod protein as tablets reduced fasting glucose and LDL-cholesterol as well as postprandial glucose concentrations in healthy, overweight adults (17) .…”
mentioning
confidence: 73%
“…Studies suggests that there are other components in fish such as fish proteins that may be beneficial to human health and affect risk factors leading to CVD, beyond n-3 fatty acids (15)(16)(17)(18) . This is supported by results from animal studies showing that fish proteins may have a lowering effect on TAG and cholesterol as well as improve glucose tolerance (19)(20)(21)(22)(23)(24)(25)(26) . In line with this, we have recently shown that supplementation with cod protein as tablets reduced fasting glucose and LDL-cholesterol as well as postprandial glucose concentrations in healthy, overweight adults (17) .…”
mentioning
confidence: 73%
“…A number of studies, using high doses of fish protein or protein hydrolysate from Atlantic salmon (15-20% of diet), have demonstrated reduced plasma cholesterol levels in Wistar rats (Hosomi et al, 2011;Liaset et al, 2009). This has been linked to increased plasma bile acid levels, and cholesterol clearance through the bile.…”
Section: Discussionmentioning
confidence: 97%
“…A cholesterol lowering effect of FPH diets compared to casein diets have previously been observed in rodents, and may be due to decreased intestinal absorption concomitant with increased hepatic excretion of cholesterol and bile [28,29]. FPH has in some rodent studies also resulted in lower plasma triacylglycerol (TAG) levels [15,30].…”
Section: Discussionmentioning
confidence: 99%